The Effectiveness of Regent Regulation Number 1 of 2019 Concerning the Online Regional Tax System in Tax Collection from a Siyasah dusturiyah Perspective (Case Study: Cipanas Tourist Attraction, Garut Regency) - Suci Mutiara Insyira; Ija Suntana; Ridwan Eko Prasetyo (al-Afkar, Journal For Islamic Studies, 2026)
This research is motivated by data on Regional Original Income (PAD) in the hotel and water tourism tax sector in Garut Regency, which still faces various implementation obstacles. This study aims to analyze the effectiveness of Garut Regent Regulation Number 1 of 2019 concerning the Regional Tax Online System, examine the perceptions of taxpayers and tax officials, and analyze it from a siyasah industrial perspective. The theoretical framework used refers to Soerjono Soekanto's theory of legal effectiveness which includes five main dimensions, namely legal substance, law enforcement, facilities and infrastructure, society, and legal culture and the siyasah industrial theory which emphasizes the principles of trust, justice, and benefit to assess the suitability of a regulation with Islamic legal values. The research method used is empirical juridical with descriptive analysis techniques through the use of secondary data and the results of field interviews. The results show that the implementation of the regional tax Online system is effective in the hotel tax sector, as indicated by the consistency of revenue realization that exceeds the target. Conversely, in the entertainment tax sector which represents water tourism, effectiveness is not optimal. This is proven to increase transparency, reporting accuracy, and monitoring effectiveness. From the perspective of industrial governance, this policy reflects the principles of trust, justice, and welfare, although it still requires strengthening in the aspects of socialization, apparatus capacity, and technological readiness.